Dynamic Activity of Histone H3-Specific Chaperone Complexes in Oncogenesis - Wen, Ting; Chen, Qiao Yi (Frontiers in Oncology, 2022)
Canonical histone H3.1 and variant H3.3 deposit at different sites of the chromatin via distinct histone chaperones. Histone H3.1 relies on chaperone CAF-1 to mediate replication-dependent nucleosome assembly during S-phase, while H3.3 variant is regulated and incorporated into the chromatin in a replication-independent manner through HIRA and DAXX/ATRX. Current literature suggests that dysregulated expression of histone chaperones may be implicated in tumor progression. Notably, ectopic expression of CAF-1 can promote a switch between canonical H3.1 and H3 variants in the chromatin, impair the chromatic state, lead to chromosome instability, and impact gene transcription, potentially contributing to carcinogenesis. This review focuses on the chaperone proteins of H3.1 and H3.3, including structure, regulation, as well as their oncogenic and tumor suppressive functions in tumorigenesis.